Evidence and Current Use of Levosimendan in the Treatment of Heart Failure: Filling the Gap - Conti N; Gatti M; Raschi E; Diemberger I; Potena L (Dove Medical Press, 2021)
Nicolina Conti,1 Milo Gatti,2,3 Emanuel Raschi,2 Igor Diemberger,1,4 Luciano Potena4 1Cardiology Unit, Department of Experimental, Diagnostic and Specialty Medicine, Alma Mater Studiorum - University of Bologna, Bologna, Italy; 2Pharmacology Unit, Department of Medical and Surgical Sciences, Alma Mater Studiorum - University of Bologna, Bologna, Italy; 3SSD Clinical Pharmacology, IRCSS Azienda Ospedaliero-Universitaria Di Bologna, Bologna, Italy; 4Cardiology Unit, IRCCS Azienda Ospedaliero-Universitaria di Bologna, Bologna, ItalyCorrespondence: Emanuel RaschiPharmacology Unit, Department of Medical and Surgical Sciences, Alma Mater Studiorum - University of Bologna, via Irnerio 48, Bologna, 40126, ItalyTel +39-051-2091802Email emanuel.raschi@unibo.itAbstract: Levosimendan is a distinctive inodilator combing calcium sensitization, phosphodiesterase inhibition and vasodilating properties through the opening of adenosine triphosphate-dependent potassium channels. It was first approved in Sweden in 2000 for the short-term treatment of acutely decompensated severe chronic heart failure when conventional therapy is not sufficient, and in cases where inotropic support is considered appropriate. After more than 20 years, clinical applications have considerably expanded across critical care and emergency medicine, and levosimendan is now under investigation in different cardiac settings (eg, septic shock, pulmonary hypertension) and for non-cardiac applications (eg, amyotrophic lateral sclerosis). This narrative review outlines key milestones in levosimendan history, by addressing regulatory issues, pharmacological peculiarities and clinical aspects (efficacy and safety) of a drug that did not receive great attention in the heart failure guidelines. A brief outlook to the ongoing clinical trials is also offered.Keywords: levosimendan, heart failure, cardiogenic shock, cardiac surgery, amyotrophic lateral sclerosis